Assessment of the Nutritional Quality of Plant Lipids Using Atherogenicity and Thrombogenicity Indices - Khalili Tilami, Sarvenaz; Kouřimská, Lenka (Nutrients, 2022)
Dietary lipids derived from plants have different compositions of individual fatty acids (FA), providing different physical and chemical properties with positive or adverse health effects on humans. To evaluate the nutritional value and assess the FA composition of various plants, the atherogenicity (AI) and thrombogenicity (TI) indices were calculated and reviewed for nine different categories of fats and oils. This included common oils, unconventional oils, nut oils originating from temperate regions, Amazonian and tropical fats and oils, chia seed oil, traditional nuts originating from temperate regions, unconventional nuts, seeds, and fruits, and their products. The main factors influencing fatty acid composition in plants are growth location, genotype, and environmental variation, particularly temperature after flowering, humidity, and frequency of rainfall (exceeding cultivar variation). The lowest AI was calculated for rapeseed oil (0.05), whereas the highest value was obtained for tucuman seeds (16.29). Chia seed oil had the lowest TI (0.04), and murumuru butter had the highest (6.69). The differences in FA composition and subsequent changes in the lipid health indices of the investigated fats and oils indicate their importance in the human diet.
Keywords: mastné kyseliny; Fats; cholesterol; plant lipids; Fatty Acids; dietní tuky; nutriční hodnota; lidé; máslo; Plant Oils; Nutritive Value; thrombogenicity index; rostliny; Butter; atherogenicity index; oleje rostlin; Plants; tuky; fatty acids; olej z řepky; Dietary Fats; Rapeseed Oil; Humans